Synthesis and evaluation of amino acid ionic liquid for enhanced oil recovery: experimental and modeling simulation studies - E. M. Mansour; R. Hosny; Ammona S. Mohamed; Fatma M. Abdelhafiz (Scientific Reports)
Abstract Recovering the remaining oil after primary and secondary extraction methods poses a significant challenge. Enhanced oil recovery (EOR) techniques, which involve injecting fluids into reservoirs, aim to increase recovery rates. Ionic liquids, known for their adaptability, are emerging as promising agents in EOR, improving oil displacement by reshaping fluid properties and interacting with reservoir rocks. This study investigates the eco-friendly amino acid ionic liquid, AAIL [G0.5 C12][Pro], for EOR applications, focusing on its characterization and performance. Using pre-prepared quaternary ammonium salt PAMAM G0.5 C12 and proline, AAIL [G0.5 C12][Pro] was synthesized and confirmed via FTIR and 1H-NMR analyses. Rheological analysis identified 7 g of AAIL [G0.5 C12][Pro] as the optimal concentration for peak performance. Laboratory sand-pack displacement experiments demonstrated an 11% increase in oil recovery at this concentration. Further, a 3D reservoir model simulation validated the enhanced oil recovery potential of AAIL [G0.5 C12][Pro]. The study introduces the novel amino acid ionic liquid [G0.5 C12][Pro], which demonstrates superior effectiveness in enhancing oil recovery through significant wettability modification and interfacial tension reduction, underscoring its potential as an effective and environmentally friendly EOR agent compared to other ionic liquids and conventional methods.